1998
DOI: 10.1002/(sici)1096-8628(19980203)75:4<367::aid-ajmg5>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

FISH and molecular studies of autosomal supernumerary marker chromosomes excluding those derived from chromosome 15: II. Review of the literature

Abstract: Using fluorescence in situ hybridization (FISH), supernumerary marker chromosomes (SMC) from all the human autosomes except chromosome 5, have now been described, most being derived from the acrocentric autosomes. This review summarizes the results of 168 cases of autosomal SMC excluding those from chromosome 15 where FISH has been used to define the chromosomal origin of the SMC and from which phenotypic information is available. Although the number of reported cases from some of the chromosomal SMC groups re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
115
0
6

Year Published

1999
1999
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(128 citation statements)
references
References 45 publications
(35 reference statements)
7
115
0
6
Order By: Relevance
“…We have therefore excluded for the purposes of the present study any cases that were recruited and analysed as part of defined SMC research protocols. 11,16,19,20 The population served by the WRGL, approximately 2.5 million, over the period of the study has been stable and has not witnessed significant changes in migration patterns as seen in other parts of the UK. The WRGL reports constitutional cytogenetic chromosome results from both perinatal and postnatal patient groups.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…We have therefore excluded for the purposes of the present study any cases that were recruited and analysed as part of defined SMC research protocols. 11,16,19,20 The population served by the WRGL, approximately 2.5 million, over the period of the study has been stable and has not witnessed significant changes in migration patterns as seen in other parts of the UK. The WRGL reports constitutional cytogenetic chromosome results from both perinatal and postnatal patient groups.…”
Section: Discussionmentioning
confidence: 95%
“…FISH was carried out using standard techniques based on a modification of Pinkel et al, 18 and the probes used have been reported previously (eg Crolla 19 and Crolla et al 20 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the risk for an abnor mal phenotype in prenatally ascertained de novo cases with sSMC is considered to be ~13% [4]. This has been refined to 7% (for sSMC from chromosomes 13, 14, 21 or 22) and 28% (for all non-acrocentric autosomes) [5] and has recently been suggested to be 26-30% [1,6]. Also, BJMG 10/1 (2007) 33-37 10.2478/v10034-007-0006-5 generally speaking, sSMC transmitted by normal sSMC carriers to their progeny are not correlated with clinical problems [7], although exceptions have been described [8].…”
Section: Introductionmentioning
confidence: 99%
“…The empirical risk for congenital anomalies is approximately 13% for randomly associated de novo SMCs, 3 -6 7% for SMCs derived from acrocentric chromosomes (excluding the 15s), and 28% for SMCs derived from nonacrocentric autosomes. 10 As a result of the high risks and many uncertainties regarding the clinical outcome, many pregnancies with de novo SMC are terminated. However, effective FISH studies can reduce uncertainties, giving affected couples a better reproductive choice.…”
Section: Introductionmentioning
confidence: 99%